Solid support synthesis of all-Rp-oligo(ribonucleoside phosphorothioate)s. - Almer, H (1996)
The first method for solid support synthesis of all-Rp-oligo(ribonucleoside phosphorothioate)s is presented as well as attempts to increase the stereoselectivity of the key step in this approach. The synthetic strategy consists of (i) a solid support synthesis procedure, using 5'-O-(4-methoxytriphenylmethyl)-2'-O-tert-butyldimethylsilyl-ri bon ucleoside 3'-H- phosphonates, that due to stereoselectivity in the condensation step, gives oligomers with mostly Sp-H-phosphonate diesters (72-89% under standard conditions), (ii) stereospecific sulfurization with S8 in pyridine to produce oligo(ribonucleoside phosphorothioate)s enriched with internucleosidic linkages of Rp configuration, (iii) treatment of the deprotected oligonucleotides with the enzyme Nuclease P1 from Penicillium citrinum, that specifically catalyses cleavage of Sp-phosphorothioate diester linkages, which leaves a mixture of oligomers having all internucleosidic linkages as Rp-phosphorothioates, and finally (iv) isolation and HPLC purification of the full length all-Rp oligomer. Mixed sequences containing the four common nucleosidic residues up to the chain length of a heptamer were synthesized. Change of N-4-protection on the cytidine building block from propionyl to N-methylpyrrolidin-2-ylidene gave a slightly improved diastereoselectivity in H-phosphonate diester formation. Increased selectivity up to 99+% was obtained with the guanosine building block when the amount of pyridine in the coupling step was reduced.